Serum 1,25-dihydroxycholecalciferol (DHVD3) and matrix metalloproteinase-2 (MMP-2) levels in women with uterine leiomyoma(S) - FATIMAH A. DAWOOD MSC; ENAS A.A. RASULC.A.B.O.G.; RAYAH S. BABAN PH.D (International Journal of Pharma and Bio Sciences, 2017)
Uterine fibroids (leiomyomas), the most common benign tumors in the female reproductive system, arise from smooth muscle cells of the uterus and contain extracellular matrix. This study was aimed to identify whether low serum 1,25-Dihydroxycholecalciferol (DHVD3) levels correlate with increased risk of uterine leiomyoma(s). So, a total of 64 women were recruited for this case-control study. For each case, fibroid size was determined according to the prolate ellipse formula. Serum 1,25-Dihydroxycholecalciferol (DHVD3), and Matrix Metalloproteinase-2 (MMP-2) levels were measured by ELISA kit. Low serum 1,25-Dihydroxycholecalciferol levels in leiomyoma patients were significantly correlated inversely with total fibroid’s size. Also, a significant difference (p<0.05) in mean level of MMP-2 was found between patients and control group. In conclusion, lower serum 1,25-Dihydroxycholecalciferol levels were inversely correlated with uterine fibroid size and the 1,25-Dihydroxycholecalciferol levels deficiency is a possible risk factor for the occurrence of uterine fibroids. Insignificant correlation was found between patient’s serum Matrix Metalloproteinase-2 and their fibroid’s size even when the level of Matrix Metalloproteinase-2 was high.